Inequality, networks, and the financing of Classic Maya political power. (September 2021) - Thompson, Amy E.; Feinman, Gary M.; Lemly, Marina; Prufer, Keith M.
Abstract: Inequality is present to some degree in all human societies. In prehispanic Mesoamerica, wealth inequality has been linked to forms of governance, where Classic Maya (250–800 CE) centers exhibit greater wealth inequality then other regions in Mesoamerica. However, how does wealth inequality vary in the Classic Maya world and, specifically, in a region on the margins of the central Maya Lowlands? Here, we examine the mechanisms that differentially drove wealth inequality at eight Classic Maya centers in a single sub-region, southern Belize, linking access to trade and the monopolization of resources with greater degrees of wealth inequality using Least Cost Path analyses and the Gini coefficient. We compare house sizes to calculate the Gini coefficient, multiproxy chronology data to determine occupational history of each center, and network analyses to model movement and transactional relationships in the region. In southern Belize, the foundation date and longevity of each center did not correlate with wealth inequality, likely because when these regional centers were established during the Classic period principals and subaltern alike were already enmeshed in the political economy and social organization of the Classic Maya. Rather, principals were supported through the fiscal financing of external resources through exclusionary exchange networks with some centers exhibiting and maintaining greater degrees of wealth inequality compared to others. Nonetheless, in the peripheral region of southern Belize high degrees of inequality, akin to those in the central Peten, were sustained. This study elucidates the ties between transactional networks, monopolization of resources, and inequities in wealth. Highlights: Wealth differentials were assessed for eight Classic Maya centers in southern Belize. Least cost paths employed to define socioeconomic networks. Centers with greater access to exchange networks had higher degrees of inequality. Degree of inequality in southern Belize parallels inequality in the Maya heartland.